2005
DOI: 10.1089/cap.2005.15.655
|View full text |Cite
|
Sign up to set email alerts
|

Child and Adolescent Suicides in Virginia: 1987 to 2003

Abstract: Guns and hanging were the principal methods of suicide. Among the antidepressants, TCAs have been the most common poisons used in suicide. Increasing age was a powerful determinant of suicide. Some patients may have stockpiled their TCAs for a while before their TCA overdose. Other suicide victims may have used TCA supplies from family members. Hence, some of the suicide victims may not have taken TCAs on a regular basis before committing suicide. Further exploration of TCA-induced suicidal thoughts is needed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
5
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 2 publications
5
5
0
5
Order By: Relevance
“…Consistent with other published studies, two control variables, female gender (Doshi et al 2005;Teplin et al 2005) and white racial category (Vieweg et al 2005) were independently associated with higher suicide ideation scores, but only in younger and not older adolescents. These results underline the importance of taking into account age, gender and racial/ethnic differences, as well as the source and type of social support when assessing mental health needs and targeting interventions for higher risk adolescents.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with other published studies, two control variables, female gender (Doshi et al 2005;Teplin et al 2005) and white racial category (Vieweg et al 2005) were independently associated with higher suicide ideation scores, but only in younger and not older adolescents. These results underline the importance of taking into account age, gender and racial/ethnic differences, as well as the source and type of social support when assessing mental health needs and targeting interventions for higher risk adolescents.…”
Section: Discussionsupporting
confidence: 90%
“…Recent evidence suggests, however, that either some of the protective factors may be changing, or risk factors are increasing. During 1980-1995 for example, suicide rates increased 126% among blacks 15-19-years-old, compared with 19% for whites (Doddakashi et al 2003;Vieweg et al 2005). In addition, suicide ideation rates have been reported as significantly higher in US Mexican, Pakistani and Vietnamese adolescent populations relative to white teens (Roberts et al 1997), although culture-specific socialization has been suggested as a source of variation in risk profiles within minority groups (Vaughn and Roesch 2003).…”
Section: Introductionmentioning
confidence: 99%
“…32 Male children were disproportionately represented among the suicide victims as reported in other studies. 8,18,33 Males are three times more likely than females to complete suicide, but females are more likely to exhibit persistent suicidal ideation and to engage in self-injury or self-harm behavior, without expressed intent to die. 8 In this study, suicide (19 cases) was the third leading cause of death and was only found in the older age groups.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][37] Es importante mencionar que en México el suicidio en menores de 10 años de edad es poco frecuente, se han registrado 115 suicidios de 1979 a 2002. Cabe resaltar que en el periodo 2003-2011 no hubo registros de suicidios en este grupo de edad.…”
Section: Discusión Y Conclusiónunclassified
“…donde es la principal forma de suicidio. 17,21,34 No obstante, este método se empleó con mayor frecuencia en los Estados de Zacatecas, Baja California Sur y Sonora.…”
Section: Discusión Y Conclusiónunclassified